2018
DOI: 10.1080/19476337.2018.1471102
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the physicochemical properties, aromas and polyphenols of not from concentrate (NFC) apple juice during production

Abstract: The effects of unit operations on the quality of not from concentrate (NFC) apple juice were investigated in this study. After the main processing steps (juicing, pre-pasteurization, homogenization and pasteurization), juice samples were collected and characterized by total soluble solid (TSS), titratable acidity (TA), pH, turbidity, non-enzymatic browning index (NEBI), color quality, aromas and phenolic constituents. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) were applied for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
(52 reference statements)
7
16
1
Order By: Relevance
“…The obtained results for pH are comparable to those documented for some fruits such as orange, kiwi fruit and apple 23 , which ranged from 3.23 to 4.22. Similar findings have been published for the apple in Poland, Tunisia and China respectively [24][25][26] . The results of TA from this study were higher than those documented by Boudabous et al 24 but similar to those reported previous studies 23, 26 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The obtained results for pH are comparable to those documented for some fruits such as orange, kiwi fruit and apple 23 , which ranged from 3.23 to 4.22. Similar findings have been published for the apple in Poland, Tunisia and China respectively [24][25][26] . The results of TA from this study were higher than those documented by Boudabous et al 24 but similar to those reported previous studies 23, 26 .…”
Section: Resultssupporting
confidence: 87%
“…Similar findings have been published for the apple in Poland, Tunisia and China respectively [24][25][26] . The results of TA from this study were higher than those documented by Boudabous et al 24 but similar to those reported previous studies 23, 26 . Acidity is one of the elements used to assess fruits quality 27 , and it gives the sour taste due to the presence of malic acid…”
Section: Resultssupporting
confidence: 87%
“…The increased L * value after thermal treatment was also observed in previous studies (Tian et al., 2018), providing the juice with brighter color and more transparent appearance. The explanation is that steaming treatment accelerated the clarification of the juice by changing their macromolecules distribution.…”
Section: Resultssupporting
confidence: 83%
“…The pH value of the TYA juice was not significant affected or slightly increased by the steaming treatment. Fruit juice is regarded as common natural buffer system containing a great number of organic acids, which provide juice with a resistance to pH change (Tian et al., 2018). However, heat treatment juices were detected lower titratable acid (TA) content and total phenol content possibly due to the thermal degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Pavun et al [2018] highlighted that the use of fruit nectar definitely lowered the phenolic content in commercial juices, which was ultimately correlated with their antioxidant activity. It was also demonstrated that not pasteurization but pre-pasteurization had a significantly stronger impact on phenolics content during processing of not from concentrate (NFC) juices [Tian et al, 2018].…”
Section: Factors Influencing the Content Of Phenolic Compounds In Appmentioning
confidence: 99%